2021
DOI: 10.1016/j.kint.2021.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, histopathological features, and graft outcome of transplant glomerulopathy in the absence of donor-specific HLA antibodies

Abstract: Transplant glomerulopathy is established as a hallmark of chronic antibody-mediated rejection in kidney transplant patients with donor-specific HLA antibodies (HLA-DSA). The clinical importance of transplant glomerulopathy in the absence of HLA-DSA is not well established. To help define this, 954 patients (encompassing 3744 biopsies) who underwent kidney transplantation 2004-2013 were studied with retrospective high-resolution HLA genotyping of both donors and recipients. The risk factors, histopathological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…A retrospective analysis of TG in 954 kidney transplant recipients (3,744 biopsies including protocol biopsies) observed TG in 10% of patients independent of HLA mismatches, and >75% of TG cases had no HLA-DSA. They concluded that iTG represents a different phenotype that had lower levels of concomitant inflammation and graft loss compared with HLA-DSA+ TG ( 52 ). In our study iTG was observed in 47.5% of indication biopsies without signs for AMR, and we could not detect significant differences in outcomes among iTG, cAMR and cAAMR during a 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of TG in 954 kidney transplant recipients (3,744 biopsies including protocol biopsies) observed TG in 10% of patients independent of HLA mismatches, and >75% of TG cases had no HLA-DSA. They concluded that iTG represents a different phenotype that had lower levels of concomitant inflammation and graft loss compared with HLA-DSA+ TG ( 52 ). In our study iTG was observed in 47.5% of indication biopsies without signs for AMR, and we could not detect significant differences in outcomes among iTG, cAMR and cAAMR during a 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it remains unclear which of these potential pathophysiologic processes are transient and do not progress to chronic irreversible injury, and which processes are deleterious, ultimately culminating in graft failure. In multiple studies on this same cohort, we showed that HLA-DSA negative ABMR/cg does not differ from ABMR/cg with HLA-DSA regarding histology or gene expression, but nonetheless has better outcome [11,19,42,43]. There is evidence supporting that the HLA-DSA negative cases represent a distinct entity, with a more transient histology of ABMR and less C4d deposition [19].…”
Section: Discussionmentioning
confidence: 65%
“…The observed multilayering of basement membranes, assessed in the first place by ultrastructural analysis, is considered to be induced by repeated, prolonged and/or sublytic endothelial damages, that are known to promote proinflammatory, procoagulant and proliferative-restorative changes of the endothelial cells and their environment [7]. While transplant glomerulopathy is not uncommon, with a cumulative incidence estimated of approximately 20% at 5 years of transplantation, and is associated with proteinuria and declining allograft function [8,9], the literature lacks an in-depth exploration of the deregulated proteins observed in this severe entity [10,11]. Changes in the extracellular matrix have been recently described by proteomics during active ABMR [12].…”
Section: Introductionmentioning
confidence: 99%